HUBUNGAN PARAMETER DECLINE CURVE ANALYSIS DENGAN PERMEABILITAS DAN API FLUIDA RESERVOIR BERDASARKAN JENIS MEKANISME TENAGA PENDORONG RESERVOIR - Saraswaty, Dhita
Decline Curve Analysis is a very popular method used to estimate reservoir’s reserve because the production data as the input data will always be available. Therefore, the trend of production decline data is success key of Decline Curve Analysis process. The constant b as the value of exponential of production decline may be one of parameters that determine the accuracy of extrapolation process. Based on the results of filed studies, it is believed that the exponential of production decline is associated with the type of reservoir driving mechanism. It is also believed that the driving mechanism that produces high value of Recovery Factor, will create high value of exponential of production decline as well. Based on the theory, Recovery Factor is influenced by the physical properties of reservoir and reservoir fluid properties. This study aims to see the effect of revervoir physical properties and reservoir fluid properties to the value of b corresponding to the process of Decline Curve Analysis. The Decline Curve Analysis in this study was conducted on the production data from reservoir simulation results of various models with the variations in reservoir driving mechanism. The physical properties of reservoir used as parameter in this study is permeability. Meanwhile, fluid’s API is used as fluid reservoir parameter. The study concludes in a relationship between permeability and exponential constants. While the ° API fluid reservoir does not give significant effect to a constant value exponentially The final results of this study can estimate the value of the constant exponential of production decline more accurately based on the value of reservoir permeability